Altering fiber density of cockscomb-like fibrous silica–titania catalysts for enhanced photodegradation of ibuprofen. (1st December 2018) - Fauzi, A.A.; Jalil, A.A.; Mohamed, M.; Triwahyono, S.; Jusoh, N.W.C.; Rahman, A.F.A.; Aziz, F.F.A.; Hassan, N.S.; Khusnun, N.F.; Tanaka, H.
Abstract: Fibrous silica–titania (FST) catalysts were synthesized by microemulsion followed by silica seed-crystal crystallization methods under various molar ratios of toluene to water (T/W). The catalysts were characterized by XRD, UV-DRS, FESEM, TEM, AFM, N2 adsorption–desorption, FTIR, and ESR. The results revealed that altering the T/W ratio affected the growth of the silica and titania and led to different size, fiber density, silica–titania structure, and number of hydroxyl groups, as well as oxygen vacancies in the FSTs, which altered their behavior toward subsequent application. Photodegradation of ibuprofen (IBP) are in the following order: FST(6:1) (90%) > FST(5:1) (84%) > FST(7:1) (79%) > commercial TiO2 (67%). A kinetics study using Langmuir–Hinshelwood model illustrated that the photodegradation followed the pseudo-first-order and adsorption was the rate-limiting step. Optimization by response surface methodology (RSM) showed that the pH, initial concentration, and catalyst dosage were the remarkable parameters in photodegradation of IBP. The FST (6:1) maintained its photocatalytic activities for up to five cycles reaction without serious catalyst deactivation, and was also able to degrade other endocrine-disrupting chemicals, indicating its potential use for the treatment of those chemicals in wastewater. Graphical abstract: Highlights: Efficient urchin-like fibrous SiO2 –TiO2 (FST) photocatalysts were well synthesized. Fiber density was altered by varying the molar composition of toluene and water. FST(6/1) catalyst gave the highest photodegradation (90%) of ibuprofen. Alternate integration of SiO2 –TiO2 dendrimeric fibers enhanced photodegradation. FST showed a good potential as a visible-light-driven photocatalyst for many EDCs.